Final report first review meeting Alluvial channel observation project (ACOP) - Mahmood, Khalid, author; Colorado State University, publisher (Colorado State University. Libraries, 1974)
Alluvial Channel Observation Project, ACOP is a Special Foreign Currency Cooperative Research Project funded by a NSF grant to Water and Power Development Authority, Pakistan. The Project was inaugurated in Pakistan in January-February, 1974, and since then considerable progress has been made in the organization, staffing and field work. A review meeting was held at Colorado State University from August 8 to August 11, 1974. This was attended by Mr. R.A. Qureshi, General Manager, Water, WAPDA and Project Manager, ACOP, and Mr. Riaz N. Tarar, Project Director and Principal Investigator, ACOP from Pakistan. The review meeting was followed by a visitation of the Pakistani scientists and the U.S. Cooperating Scientist to various Federal Agencies interested in the mechanics of alluvial channels. The review meeting and the following visitation was sponsored by the supplementary a NSF grant to Colorado State University. This completion report narrates the discussions and the decisions of the review meeting. It also covers the visit of the Pakistani scientists to U.S. Federal Agencies.
CER 74-75KM7.
To Office of International Programs, National Science Foundation.
September 1974.
Keywords: Channels (Hydraulic engineering); Sediment transport -- Pakistan; Canals -- Pakistan